Ecobricks as A Sustainable Solution: Designing an Eco-Friendly Reading Garden to Reduce Plastic Waste - Ariyani, Dwi; Arini, Resti Nur; Lestari, Rini Trisno; Kurnia, Fadli (Universitas Serang Raya, 2024)
The increasing population from year to year has led to a rising demand for housing. Alongside this population growth, there has been a concurrent increase in waste production, particularly plastic waste discarded into the environment. In order to achieve SDG Goal 11, community engagement activities are being conducted. These activities occur within the Ecovillage Karawang community, a network dedicated to environmental preservation and plastic waste recycling. The methods employed include surveys, literature reviews, and the application of Ecobricks. Previously, community engagement activities involved providing tools for plastic shredding and Ecobrick production, but these were limited to residual plastic bottles and hard plastics. This community engagement project (PKM) aims to design and construct a 2.5m x 2.5m reading garden using Ecobricks as a building material. The aim of this PKM program is to provide multiple benefits through a single activity, specifically the application of Ecobricks as a construction material and the reduction of plastic waste through the reuse of ecobricks. This PKM project determined that 105 kg of plastic waste, including wrappers from candies, beverage sachets, plastic bags, and packaging, were used in constructing the reading garden. It, of course, contributes significantly to reducing plastic waste in the environment.